Mesopontine cholinergic inputs to midbrain dopamine neurons drive stress-induced depressive-like behaviors. Issue 1 (December 2018) - Fernandez, Sebastian; Broussot, Loïc; Marti, Fabio; Contesse, Thomas; Mouska, Xavier; Soiza-Reilly, Mariano; Marie, Hélène; Faure, Philippe; Barik, Jacques
Abstract Stressful life events are primary environmental factors that markedly contribute to depression by triggering brain cellular maladaptations. Dysregulation of ventral tegmental area (VTA) dopamine neurons has been causally linked to the appearance of social withdrawal and anhedonia, two classical manifestations of depression. However, the relevant inputs that shape these dopamine signals remain largely unknown. We demonstrate that chronic social defeat (CSD) stress, a preclinical paradigm of depression, causes marked hyperactivity of laterodorsal tegmentum (LDTg) excitatory neurons that project to the VTA. Selective chemogenetic-mediated inhibition of cholinergic LDTg neurons prevent CSD-induced VTA DA neurons dysregulation and depressive-like behaviors. Pro-depressant outcomes are replicated by pairing activation of LDTg cholinergic terminals in the VTA with a moderate stress. Prevention of CSD outcomes are recapitulated by blocking corticotropin-releasing factor receptor 1 within the LDTg. These data uncover a neuro-circuitry of depressive-like disorders and demonstrate that stress, via a neuroendocrine signal, profoundly dysregulates the LDTg. Dopamine neurons in the ventral tegmental area (VTA) are implicated in depressive-like behaviors. Here, the authors show that cholinergic inputs to the VTA from the laterodorsal tegmentum regulate intrinsic plasticity of VTA DA neurons to mediate stress-induced depressive-like behaviors.